2022
DOI: 10.3389/frai.2022.910049
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Real-World Monitoring of the Heart Rate Variability in Amyotrophic Lateral Sclerosis

Abstract: AimsCardiovascular dysautonomia may impact the quality of life and survival in amyotrophic lateral sclerosis (ALS). Such dysfunction is not systematically assessed in these patients. Wearable devices could help. The feasibility of a wearable biosensor to detect heart rate variability (HRV), a physiological marker of sympathovagal balance, was studied for the first time in real-world settings in ALS.MethodsFive ALS patients (two early/three late; one bulbar-onset; mildly-to-moderately disabled) and five age/sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…In terms of SDNN, values within the normal range in our healthy group were observed, but these were significantly lower in the ALS group (30.07 ms). This aligns with the findings of Brown et al [33], who, after measuring for 3 days, reported similar results. Values below 35 are considered a high health risk due to ANS weakness [16], and an SDNN interval below 19 ms is associated with imminent death within a year [24].…”
Section: Discussionsupporting
confidence: 93%
“…In terms of SDNN, values within the normal range in our healthy group were observed, but these were significantly lower in the ALS group (30.07 ms). This aligns with the findings of Brown et al [33], who, after measuring for 3 days, reported similar results. Values below 35 are considered a high health risk due to ANS weakness [16], and an SDNN interval below 19 ms is associated with imminent death within a year [24].…”
Section: Discussionsupporting
confidence: 93%
“…In a recent small pilot study, the researchers carried out HRV measurements over three days using a non-invasive biosensor. They emphasized the necessity of following the patients from the perspective of obtaining valuable data about non-motor symptoms, but also to better monitor them using non-invasive methods in such fragile individuals [47].…”
Section: Cardiovascular Dysfunctionmentioning
confidence: 99%
“…Such an already wide spectrum of cells participating in the disease may further extend upon appreciation that subclinical alterations in autonomic control of organ functions are frequently present in ALS patients and that the early manifestations of ALS occur in peripheral tissues and involve muscle atrophy and weakness, NMJ alterations, and metabolic changes (Shimizu et al, 1994;Baltadzhieva et al, 2005;Pavlovic et al, 2010;Merico and Cavinato, 2011;Shimizu et al, 2011;Shimizu, 2013;Dalla Vecchia et al, 2015;De Maria et al, 2015;Piccione et al, 2015;Nolano et al, 2017;Rosenbohm et al, 2017;Pimentel et al, 2019;Silveira et al, 2022). Analysis of heart rate variability (HRV) (Pimentel et al, 2019;Brown et al, 2022) and systolic arterial pressure variability (SAPV) revealed altered sympatho-vagal balance (Moreau et al, 2012;Xia et al, 2022), and microneurography demonstrated a reduced spontaneous activity of sympathetic efferences in sciatic nerves, suggestive of neurodegeneration (Donadio and Liguori, 2015). The same trial has demonstrated that SOD1 G93A mice show a 24% decrease in TH expression in adrenal glands (Kandinov et al, 2013).…”
Section: Introductionmentioning
confidence: 96%